Laparoscopic Resection of a Torsed Big Myoma at 16th Weeks of Gestation - Derya Akdağ Cırık; Özgür Koçak; Eylem Ünlübilgin; Metin Altay; Orhan Gelişen (Medical Network, 2016)
Myomas are the most common benign tumors of the uterus; however, only 1% to 4% of women were diagnosed with myoma during pregnancy. Although a majority of myomas do not cause any problems during pregnancy and rarely present with torsion or necrosis, myomas might lead to an acute abdomen, which then indicate need for an urgent myomectomy. There are various causes for an acute abdomen during pregnancy, and it is not always easy to make the definitive diagnosis with non-invasive diagnostic tools such as ultrasonography. Because the uterus displaces the intra-abdominal organs during pregnancy, diagnosis of a surgical emergency may be delayed and, consequently, increase maternal morbidity and mortality. If a surgical emergency is indicated, laparoscopy is a safe alternative to laparotomy during pregnancy, requiring a shorter hospital stay and less analgesic; therefore, all surgeons and gynecologists should be able to perform a laparoscopy when needed in each trimester of pregnancy. Herein, we report a 31-year-old primigravid woman presented with an acute abdomen at 16 weeks gestation. Ultrasound examination revealed a nearly 10 cm myoma at the right side of the uterine fundus. Suspecting a torsed myoma, an urgent diagnostic laparoscopy, which revealed a large, torsed, subserous myoma with a 2cm base, was performed. Laparoscopic resection and morcellation was done successfully. No intra-operative or post-operative complications were encountered, and the woman gave birth to a healthy infant at term. By presenting this case, we suggest the safe use of laparoscopic myomectomy of a relatively big myoma even in the second trimester of pregnancy.